Validation of Monte Carlo simulation of neutron production in a spallation experiment. (June 2015) - Zavorka, L.; Adam, J.; Artiushenko, M.; Baldin, A.A.; Brudanin, V.B.; Bukhal, O.; Caloun, P.; Chilap, V.V.; Furman, W.I.; Husak, K.; Kadykov, M.G.; Katovsky, K.; et al.
Highlights: Uranium spallation target was irradiated by up to 4 AGeV deuteron beams. Neutron production was investigated through ( n, γ ), ( n, f ), and ( n, 2 n ) reactions in nat U. Reaction rates were also calculated employing the MCNPX 2.7.0 code. Agreement between experiment and simulation of neutron-induced reactions was found. Overestimation in simulation of production of charged particles is discussed. Abstract: A renewed interest in experimental research on Accelerator-Driven Systems (ADS) has been initiated by the global attempt to produce energy from thorium as a safe(r), clean(er) and (more) proliferation-resistant alternative to the uranium-fuelled thermal nuclear reactors. The ADS research has been actively pursued at the Joint Institute for Nuclear Research (JINR), Dubna, since decades. Most recently, the emission of fast neutrons was experimentally investigated at the massive ( m = 512 kg) natural uranium spallation target QUINTA . The target has been irradiated with the relativistic deuteron beams of energy from 0.5 AGeV up to 4 AGeV at the JINR Nuclotron accelerator in numerous experiments since 2011. Neutron production inside the target was studied through the gamma-ray spectrometry measurement of natural uranium activation detectors. Experimental reaction rates for ( n, γ ), ( n, f ) and ( n, 2 n ) reactions in uranium have provided valuable information about the neutron distribution over a wide range of energies up to some GeV. The experimental data were compared to the predictions of Monte Carlo simulations using the MCNPX 2.7.0 code. The results are presented and potential sources of partial disagreement are discussed later in this work.